Prevalence of group A β-hemolytic streptococcal throat carriage and prospective pilot surveillance of streptococcal sore throat in Ugandan school children. (April 2020) - DeWyer, Alyssa; Scheel, Amy; Webel, Allison R.; Longenecker, Chris T.; Kamarembo, Jennipher; Aliku, Twalib; Engel, Mark E.; Bowen, Asha C.; Bwanga, Freddie; Hovis, Ian; Chang, Aileen; Sarnacki, Rachel; et al.
Highlights: Group A β-hemolytic Streptococcus (GAS) rates seen in Uganda are higher than results pooled globally. This has implications for primary prevention of GAS. GAS was universally susceptible to penicillin and trimethoprim–sulfamethoxazole. Further knowledge of the acute streptococcal pharyngitis burden is essential. Abstract: Objectives: Group A β-hemolytic Streptococcus (GAS), also known as Streptococcus pyogenes, is responsible for an annual 600 million cases of acute pharyngitis globally, with 92% of those infections occurring in low-resource settings. Further knowledge of the acute streptococcal pharyngitis burden in low-resource settings is essential if serious post-streptococcal complications – rheumatic fever (RF) and its long-term sequel rheumatic heart disease (RHD) – are to be prevented. Methods: Two studies were conducted in school-aged children (5–16 years): a cross-sectional study of streptococcal pharyngeal carriage followed by a prospective cohort study of streptococcal sore throat over 4 weeks from March to April 2017. Results: The cross-sectional study revealed an overall prevalence of GAS carriage of 15.9% (79/496, 95% confidence interval 12.8–19.5%). Among 532 children enrolled in the prospective cohort study, 358 (67%) reported 528 sore throats, with 221 (41.1%) experiencing at least one GAS-positive sore throat. The overall GAS-positive rate for sore throat was 41.8% (221/528). Conclusions: The GAS pharyngeal carriage rates seen in Uganda (15.9%, 95% confidence interval 12.8–19.5%) are higher than the most recent pooled results globally, at 12% (range 6–28%). Additionally, pilot data suggest a substantially higher percentage of sore throat that was GAS-positive (41.8%) compared to pooled global rates when active recruitment is employed.